Advancing towards an understanding of the relationship between culture and agrobiodiversity. A case study in Mapuche territory, southern Chile. Issue 1 (31st December 2022) - Spirito, Florencia; Vieli, Lorena; Montalba, René
ABSTRACT: Biocultural diversity embraces the dynamic, place-based and complex relationship between biological and cultural diversity. Several studies describe a direct, positive relationship between biological and cultural diversity; however, this relationship is usually entwined within a particular socio-ecological context. We explored the relationship between cultural diversity and agrobiodiversity in smallholder farming systems in a rural landscape in south-central Chile considered as Indigenous Mapuche ancestral territory. We hypothesized a positive correlation between cultural diversity and agrobiodiversity in this context. We estimated three levels of agrobiodiversity: (i) subsystems (vegetable garden, orchard, chacra, annual crops and natural places), (ii) plant species and (iii) plant landraces. In our study area, smallholders form three distinctive groups based on their cultural origin: (i) Indigenous Mapuche, (ii) Chileans and (iii) foreigners. Using diversity indices, we explored patterns across 15 focal landscapes (3.14 km2). Contrary to our hypothesis, we found a negative correlation between cultural diversity and agrobiodiversity, as while Mapuche farms presented the highest agrobiodiversity and were dominant in most focal landscapes, Chilean and foreign-owned farms were mostly dominated by monocultures. This negative link highlights the need to further study this relationship considering different socio-ecological aspects from a historical perspective, as well as from a socio-political point of view. Understanding the complex interactions between culture and biodiversity could help us in facing current challenges such as biodiversity loss, cultural homogenization and reducing conventional agriculture impacts.